Investigation of the Mechanical Properties of Thermoplastic Materials Influenced by Different Chemicals - Sohrab Asefi; Marzieh Nejatifard; Samaneh Kayyal; Sima Shahabi (Galenos Yayinevi, 2024)
Objective: The quality of orthodontic forces in aligners is mainly influenced by their mechanical properties. At present, there is insufficient information on how environmental factors affect the mechanical function of aligners, and studies have shown that patients do not pay enough attention to removing aligners while eating and drinking. Therefore, in this study, we investigated the effect of different chemicals on the mechanical properties of thermoplastic materials. Methods: In this study, 175 thermoplastic samples from Easy-Vac gasket (3A Medes, Korea) were prepared, and their chemical composition, tensile strength, and hardness before and after exposure to solutions of orange juice, Cola, chlorhexidine mouthwash, and distilled water were measured. One-Way analysis of variance (ANOVA), Tamhane's test, and Tukey's test were used for statistical analysis. Results: The tensile strength of the sheets increased with continuous exposure to orange juice and chlorhexidine mouthwash, and their hardness decreased with continuous exposure to carbonated beverages. There was no change in the chemical composition of the samples after exposure to different chemicals. Conclusion: Although these changes are statistically significant, they do not have a significant effect on the result of aligner performance. Therefore, the only concern is the cariogenicity of orange juice and Cola during treatment with aligners and the administration of chlorhexidine mouthwash.